Chemically Modulated Synthesis of UiO‐66(X) for Catalytic Transfer Hydrogenation of Cinnamaldehyde. Issue 31 (18th August 2022) - Yin, Dongdong; Li, Chuang; Liu, Jinxuan; Liang, Changhai
Abstract: It is of great significance to produce allylic alcohols, a fundamental intermediates in industrial organic synthesis, through hydrogenation of α, β‐unsaturated aldehydes. The development of catalytic transfer hydrogenation (CTH) to improve reaction selectivity is critical and still a major challenge. In this work, we used UiO‐66 as precursor, hydrochloric acid and monocarboxylic acid as modulators to synthesized a series of materials named UiO‐66(X). A deep investigation into the influence of modulators on the composition, morphology, and physical structure of UiO‐66(X) was presented. Most importantly, the UiO‐66(TFA) with continuous Zr−O−Zr sites as active centers both realized high conversion of cinnamaldehyde and excellent selectivity to cinnamyl alcohol (97 %) in the CTH of cinnamaldehyde and possessed good reusability and chemical stability. Abstract : The introduction of monocarboxylic modulators and HCl had a great impact on the morphology, composition and physical structure of UiO‐66(X). The reaction between cinnamaldehyde and 2‐propanol mainly happened on continuous Zr−O−Zr site on framework with high activity and selectivity, and the oxygen atoms mostly coming from μ3 ‐OH.